Quantitative analysis of thyroid gland blood supply in children and adolescents - Hakan Cebeci; Zuhal Bayramoğlu; Mehmet Öztürk; Emine Uysal (Genel Tıp Dergisi)
Aim This study aims to determine the reference vascularization index (VI) values for the thyroid gland in healthy children and adolescents using Super microvascular imaging (SMI). It was also investigated the correlation between thyroid vascularity and thyroid lobe volumes, age, sex, weight, height, and body mass index (BMI). Material and Methods One hundred and twenty-four children and adolescents without a thyroid gland, systemic disease, and medical history affecting the thyroid gland were included in the study. Participants with abnormal thyroid function tests were excluded from the study. Age, gender, height, and weight were recorded before ultrasonography and SMI examinations. After the grayscale ultrasonography, VI values for each participant were obtained using SMI. The association between the VI and thyroid lobe volumes, age, sex, weight, height, and BMI values were analyzed. Results Median values of the age, height, weight, and BMI of 124 participants were 10 (6-12) years, 1.3 (1.2-1.52) m, 30.5 (21-47) kg, 17.55 (15.37-21.14) kg/m2, respectively. Median (IQR) values of the left and right thyroid lobe volumes were 1.4 (0.9-2.07) mL and 1.9 (1.2-3.07) mL, respectively, and the mean VI value was 5.31±1.84%. There was no significant association of VI values with the thyroid lobe volume. Also, there was no relation between the mean VI values and the auxological parameters. Conclusion This study defines the VI values of thyroid glands in healthy adolescents and children. It also demonstrated no correlation between VI values of the thyroid gland and thyroid lobe volume, sex, age, weight, height, and BMI.